PERBANDINGAN KADAR LOGAM KADMIUM (Cd) DALAM URIN PEROKOK AKTIF DAN PASIF DI TERMINAL KOTA PADANG - Dina Putri Mayaserli; Julia Sri Rahayu (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Smoking is an activity that is familiar to us in everyday life. Cigarette smoke caused by active smokers to harm the health of the smokers themselves and passive smokers. Cadmium (Cd) is one of the metal compounds contained in tobacco, the higher the level and the longer the exposure, the greater the toxic effect will be given. Metal cadmium (Cd) can cause interference and even able to cause damage to the system that works kidney. Then the rest of metabolism is excreted through the urine. This study aims to determine the ratio of levels of cadmium (Cd) in the urine of active and passive smokers. The type of this research is descriptive observational research with survey method that aims to know the level of Cd in active and passive smoking urine. Determination of cadmium content (Cd) by SSA method (Atomic Absorption Spectrophotometry). Based on urine on active smokers the highest levels of cadmium metal (Cd) were 0.038 mg / L and the lowest cadmium (Cd) content was 0.026 mg / L. in the urine of passive smoking the lowest cadmium (Cd) content is 0.014mg / L and the highest cadmium level is 0.090 mg / L Then tested Mann Whitney Test where the value is 0.028 then p> 0.05 so Ho is accepted and it can be stated that there is no difference cadmium metal content (Cd) in the urine of active smokers and passive shops diterminal padang city